Winnipeg Chinatown: Demographic, Ecological and Organizational Change, 1900-1980 - Baureiss, Gunter; Driedger, Leo (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1982)
This article focuses on the Chinese of Winnipeg as a sub-community within the larger community. It traces the demographic, the spatial and the organizational changes which have taken place in the past eight decades. Substantial changes have occurred: from a segregated, traditional community centring around Chinatown to a modern community that has dispersed into other areas of the city. Canadian immigration legislation, which tended to exclude families, played a major role informing the early 'bachelor' community. The Chinese Immigration Act of 1923 virtually stopped Chinese immigration, and the repeal of this Act in 1947 and subsequent relaxation of immigration laws permitted the entry of a different type of Chinese immigrant. While the demographic and ecological changes are interesting, the distinctiveness of the Chinese experience produced two separated periods of organizational development. The early period was characterized by the formation of transplanted, though modified, traditional organizations; the later period was characterized by the emergence of functional specific organizations.